1971
DOI: 10.21236/ad0732367
|View full text |Cite
|
Sign up to set email alerts
|

Seafloor Penetration Tests: Presentation and Analysis of Results

Abstract: A series of eleven in situ penetration tests ,was conducted' 'by the Naval Civil Engineering Laboratory (NCEL) at two seafloor sites. The objectives 6f these tests were to illustrate the, capabi-itie ; of existing penetration evaluation equipment and to acquire data for use in evaluating a series of. proposed penetration ,prediction techniques. The tests consisted of allowing two types of ,objects to free-fall into, the-seafloor with the accelerations experienced by the objects during penetration being recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1973
1973
2010
2010

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…This could lead to systematic differences in strength separate from disturbance effects. However, on the basis of previous research on vane rotation rate effects (Migliore and Lee, 1971; Halwacks and Monney, 1972) , it appears as if these systematic differences are minimal (less than ten percent change in strength) . The residual negative pore pressure was measured with a device consisting of a pressure transducer connected to a ceramic disk with a nominal air penetration pressure of one bar.…”
Section: Laboratory Testsmentioning
confidence: 95%
“…This could lead to systematic differences in strength separate from disturbance effects. However, on the basis of previous research on vane rotation rate effects (Migliore and Lee, 1971; Halwacks and Monney, 1972) , it appears as if these systematic differences are minimal (less than ten percent change in strength) . The residual negative pore pressure was measured with a device consisting of a pressure transducer connected to a ceramic disk with a nominal air penetration pressure of one bar.…”
Section: Laboratory Testsmentioning
confidence: 95%
“…The sediment penetration resistance was obtained by numerically integrating the Poncelet equation after calculating or assuming a number of sediment properties: a frontal dynamic shear strength of twice the static undrained shear strength shown in Figure 6, (Migliore and Lee, 1971;True, 1975), the side-resistance equalled the frontal dynamic shear strength reduced by a factor of four-fifths (representing a strength sensitivity of 5), friction angle, and mass bulk density. Of the three methods proposed, Valent and Lee concluded that insertion into drilled holes is the best technique for high-level waste disposal because virtually any burial depth can be attained and the hole can be filled behind the waste.…”
Section: Prediction Of Penetration Depthmentioning
confidence: 99%
“…Migliore and Lee (1971) describe the successful use of the Naval Civil Engineering Laboratory's heavy, free-falling dynamic penetrometer, and Dayal and Allen (1973) report on the design of a dynamic cone penetrometer. Texas A & M University and the Sandia Corporation have been experimenting for several years with self-contained, telemetering, dynamic cone penetrometers that utilize accelerometers to measure the resistance to penetration of the device.…”
Section: In Situ Measurementsmentioning
confidence: 99%